2007
DOI: 10.1016/j.drugalcdep.2006.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Training and fidelity monitoring of behavioral interventions in multi-site addictions research

Abstract: AIMS-Methods for the training and fidelity monitoring of behavioral interventions in multi-site addictions research are reviewed, including five published studies and seven ongoing studies sponsored by the National Institute on Drug Abuse-funded Clinical Trials Network.METHODS-Methods are categorized and reviewed consistent with a technology model of treatment delivery. Topics include: therapist selection, training, certification, and supervision; selection, training, and certification of supervisors; scales a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 30 publications
0
105
0
Order By: Relevance
“…This finding demonstrates that the reporting of psychometric qualities in the complex, face‐to‐face health behaviour change interventions included in this review, may not be as infrequent as previously suggested in different populations (Baer et al ., 2007; Breitenstein et al ., 2010; Maynard et al ., 2013; Rixon et al ., 2016). However, not all studies reported psychometric qualities, and fewer reported implementation qualities, despite the importance of psychometric and implementation qualities (Gearing et al ., 2011; Glasgow et al ., 2005; Holmbeck & Devine, 2009; Lohr, 2002; Stufflebeam, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This finding demonstrates that the reporting of psychometric qualities in the complex, face‐to‐face health behaviour change interventions included in this review, may not be as infrequent as previously suggested in different populations (Baer et al ., 2007; Breitenstein et al ., 2010; Maynard et al ., 2013; Rixon et al ., 2016). However, not all studies reported psychometric qualities, and fewer reported implementation qualities, despite the importance of psychometric and implementation qualities (Gearing et al ., 2011; Glasgow et al ., 2005; Holmbeck & Devine, 2009; Lohr, 2002; Stufflebeam, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This advocacy for EBPs in substance abuse treatment is key to successful adoption and fidelity. 48,49 Indeed, a particularly important barrier to the implementation of EBPs are unsupportive state, local, and federal mental health authority administrative practices and policies. 15 The most prevalent examples are lack of a long-term vision, lack of agreement on desired outcomes, lack of penalties for non-evidenced-based practices, short-term horizons for policy planning, political mandates on competing public-sector priorities, resource limitations, and uncertainty associated with change and untoward events.…”
Section: Discussionmentioning
confidence: 99%
“…829), is an important focus of implementation research for several reasons. Providers must understand the program model elements and have the skills to implement the elements faithfully (Baer et al, 2007;Drake, Bond, & Rapp, 2006;Fixsen, Naoom, Blase, Friedman, & Wallace, 2005). Although provider competence is considered important, the relationship between competence and clinical outcome is not always direct.…”
Section: Introductionmentioning
confidence: 99%